Las candidaturas políticas femeninas en Brasil y México : una discusión sobre igualdad política - Viorato López, Erika Cecilia (Corporación Universitaria Americana, 2022)
This book is the partial result of a research project called "Female electoral candidacies transformed into marketing products and fake news against female candidates: a comparative analysis between Brazil, Colombia and Mexico". The growing female participation in decision making in Latin America invites us to read with more patience and caution the phenomenon of the emergence of a type of feminization of politics. Two countries with trajectories marked by political scandals and corruption, such as Brazil and Mexico, show that if it was difficult for women to become protagonists as political subjects - note the feminist movements of the 70s, 80s and 90s and the recent achievements in terms of public policies for the protection of women - it is not very difficult to understand the difficulty that these women faced and still face to become protagonists in the political scenario of their countries, i.e. political actors. Therefore, this book reveals only some aspects of the political path that these women must face on a daily basis in order to gain access to spaces of power.